Student Employment as a Model for Experiential Learning. (March 2018) - Fede, Jacquelyn H.; Gorman, Kathleen S.; Cimini, Maria E.
Background: Evidence suggests experiential learning promotes the development of a range of transferrable skills including communication, responsibility, and social skills. However, many students are unable to participate in internships or other common forms of experiential education because they need to work for pay. University employment has been positively associated with academic success, but less is known about its potential to develop transferrable skills.Purpose: This evaluation assessed the outcomes and experiences of former student workers employed by the Supplemental Nutrition Assistance Program Outreach project in a paid, university position.Methodology/Approach: Former workers were surveyed regarding grade point average and graduation, employment and post-graduate education, transferrable skill development, and civic behaviors and attitudes.Findings/Conclusions: Former workers reported growth on transferrable skills (e.g., communication, problem-solving), civic behaviors, and attitudes and qualitatively attributed these gains to their work as outreach workers, particularly in terms of interacting with diverse clients in the community. Results suggest benefits associated with structuring meaningful experiences in university jobs similar to those observed in other experiential education settings.Implications: University employment may be a viable route for promoting transferrable skill development. Greater consideration of employment opportunities that foster partnerships between the institution and the community may benefit the university, community, and students.